Menanamkan Karakter Dalam Pembelajaran Tari Dengan Model Project Based Learning: Study Action Research - Kholifah, Zahrah Luthfi; Budiman, Agus (Mahesa Research Center, 2024)
Indonesia has a variety of cultural arts, one of which is a wealth of traditional dance arts that are spread across various regions in Indonesia and it is important to bring them closer to the current generation through dance lessons at school which can help instill a sense of love for the country in students. The importance of instilling a sense of love for the homeland helps them shape the character of national identity, maintain local wisdom, strengthen their sense of nationalism, defend the country, motivation to study, and their desire to serve the Indonesian nation, including students studying in Indonesian schools such as the Indonesian school in The Hague, Netherlands. This research aims to obtain data and descriptions of learning outcomes to introduce traditional Indonesian dance to students at the Indonesian Middle School in The Hague, Netherlands through dance subjects using the Project Based Learning learning model so that it can instill the character of love for the country in students. This research was carried out using classroom action research through three main stages, namely: pre-action, action, and post-action with a total of 10 students. Research data was obtained by observation, interviews and action tests. Research data was analyzed based on a qualitative approach. The results of the research show that there are positive changes from the Project Based Learning learning model towards learning dance subjects to instill a sense of love for the country, students can create creative dance work as the final result of the project assignment given. By implementing the Project Based Learning model, students' knowledge increases so they can become more familiar with traditional dance arts in Indonesia.